STRATEGI KOMUNIKASI PEMASARAN HERBALIFE DALAM MEMPERTAHANKAN LOYALITAS KONSUMEN DI PEKANBARU - Sabila, Siti Zakkiyah; Lubis, Evawani Elysa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
PT Herbalife is a company with a fitness solution that also has a business opportunity in it. Multi level marketing (MLM) marketing system. The way to communicate from the seller to the consumer is the first thing that is seen in changing the attitude of the prospective customer so that it will create comfort and of course induce a change in attitude from the consumer. This study aims to find out how Herbalife's personal selling, sales promotion, and word of mouth strategies in maintaining consumer loyalty in Pekanbaru. Therefore, the authors are interested in seeing how the marketing communication strategy that is done by Herbalife in maintaining consumer loyalty, amid the competition of nutritional products that are very many in Pekanbaru. This research uses a qualitative method, namely the collection of data obtained based on the reality of the data in the field through observation, interviews, and documentation of research subjects are 4 Herbalife informants and 4 supporting informants selected using a purposive technique. To analyze the results of this study using interactive data analysis techniques, while the technique of checking the validity of the data through extended participation, increased perseverance, and triangulation. Based on the results of the writer's observation and interviews in the field, Herbalife Pekanbaru uses their marketing communication strategies namely personal selling, sales promotion and word of mouth to maintain consumer loyalty. The results of this study indicate that Herbalife's marketing communication strategy in maintaining consumer loyalty in Pekanbaru using personal sales, sales promotions and word of mouth communication. The marketing communication strategy in the form of personal selling by Herbalife Pekanbaru is more to an approach that uses interpersonal communication which emphasizes more on a personal approach that will eventually lead to repeated sales and purchases. Marketing communication strategies in the form of sales promotion conducted by Herbalife Pekanbaru by providing promotions can create loyal customers with limited edition gifts and certain qualifications with free holiday gifts which will also increase purchases so that consumers increasingly love the product. Marketing communication strategy in the form of word of mouth by Herbalife Pekanbaru because word of mouth can make these consumers also recommend to others because Herbalife has a very good product that can meet the needs and desires of its consumers. Keyword: Marketing Communication Strategy, Herbalife Pekanbaru, Consumer Loyalty